Estimation of ALP, GPT and GOT Activities in Iraqi Patients Female With Breast Cancer - AL-Mashhadani, Z. I.; Mukhlis, A. J. A.; AL-Faraji, A. S. A-Razaq (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
To investigate the activity and role of certain enzyme markers in 30 patients female with breast cancer (non-treated, treated, and treatment with recovered).The serum activity of enzyme tumor markers (ALP, GPT and GOT) of (30) patients with breast cancer, and (7) healthy control subjects by using statistical analysis: There is significant difference higher in activity of serum enzyme tumor markers (ALP, GPT, and GOT) in all patients as compared with healthy control